Interobserver variation in the diagnosis of fibroepithelial lesions of the breast: a multicentre audit by digital pathology. Issue 8 (13th February 2018) - Dessauvagie, Benjamin F; Lee, Andrew H S; Meehan, Katie; Nijhawan, Anju; Tan, Puay Hoon; Thomas, Jeremy; Tie, Bibiana; Treanor, Darren; Umar, Seemeen; Hanby, Andrew M; Millican-Slater, Rebecca
Abstract : Aim: Fibroepithelial lesions (FELs) of the breast span a morphological continuum including lesions where distinction between cellular fibroadenoma (FA) and benign phyllodes tumour (PT) is difficult. The distinction is clinically important with FAs managed conservatively while equivocal lesions and PTs are managed with surgery. We sought to audit core biopsy diagnoses of equivocal FELs by digital pathology and to investigate whether digital point counting is useful in clarifying FEL diagnoses. Method: Scanned slide images from cores and subsequent excisions of 69 equivocal FELs were examined in a multicentre audit by eight pathologists to determine the agreement and accuracy of core needle biopsy (CNB) diagnoses and by digital point counting of stromal cellularity and expansion to determine if classification could be improved. Results: Interobserver variation was high on CNB with a unanimous diagnosis from all pathologists in only eight cases of FA, diagnoses of both FA and PT on the same CNB in 15 and a 'weak' mean kappa agreement between pathologists (k=0.36). 'Moderate' agreement was observed on CNBs among breast specialists (k=0.44) and on excision samples (k=0.49). Up to 23% of lesions confidently diagnosed as FA on CNB were PT on excision and up to 30% of lesions confidently diagnosed as PT on CNB were FA on excision. Digital point counting did not aid in the classification of FELs. Conclusion: Accurate and reproducible diagnosis of equivocal FELs is difficult, particularly on CNB, resulting in poor interobserver agreement and suboptimal accuracy. Given the diagnostic difficulty, and surgical implications, equivocal FELs should be reported in consultation with experienced breast pathologists as a small number of benign FAs can be selected out from equivocal lesions.